POTENCIALIZANDO A PACIFICAÇÃO SOCIAL: PROJETO MEDIAÇÃO DE CONFLITOS NA VILA CRUZEIRO - Rosa, Conrado P. d.; Rauber, Tassia; Jardim, Reginaldo L.; Escobar, Juliana; Totti, Gabriela; Barbosa, Dúnia; Bonotto, Ana C. G. (Salão do Conhecimento, 2013)
Resumo